Effect of Calcium Hardness on Corrosion Rate of Domestic Water Galvanized Steel Pipes - J. Al –Atia, Mohammed Hussein (Nahrain University College of Engineering Journal, 2015)
Galvanized steel pipes are the main material in the implementation of domestic water distribution networks throughout Iraq. To study the variables affecting their corrosion, mathematical relationship for the calculation of corrosion rate was derived in terms of dissolved oxygen concentration, flow velocity and temperature based on the principles of mass transfer and electrochemistry , to add the effect of the calcium hardness to this relationship, experiments were conducted for measuring the corrosion rate in a straight 18.5 mm ID pipe flow of water at velocities ranged between 0.18 and 1.21 m/sec for three types of water (hard , moderate and soft). The results Shows the importance of calcium hardness on inhibiting corrosion process for more than five times in hard water compared to that in soft water also an exponential relationship between calculated to experimentally corrosion rate and calcium hardness concentration was obtained. Introducing this relationship as a correction factor for derived relationship sounded the accuracy of calculated corrosion rate results up to more than 90%.This relationship could expect and explain the disparity in the service life of these networks.